Rational Choice, Land Conflict in Nagekeo, Regional Election of Nagekeo in 2018 - Fransiskus Xaverius; Indah Novitasari (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2020)
This study aims to examine the rational choices of the Lape tribe community in 2018’s local elections as an implication of land conflict in Nagekeo. Land conflicts in Nagekeo have occurred since 2007, as a result of the formation of the New Autonomous Regions (DOB) which involves the government and indigenous peoples. Rational choice analysis based on the principle of profit and loss, that used to explain social phenomena by assuming that each actor will act as the level of the actor and choose the alternatives that are believed to bring beneficial social outcomes. The research is based on a qualitative research perspective, with the method of data collection in the form of interviews with a number of tribal functionaries, community leaders and regional leaders who are suspected of having involvement in land conflicts. The results of the study show that the behavior of choosing Lape Tribe in the 2018 is based on factors of emotional closeness to candidates, preference for non-involvement prospective candidates in land conflicts, candidates' efforts in carrying out development changes, and candidates efforts to manage and resolve conflicts through non-litigation channels. From these results it can be seen that the element of profit and loss in resolving land conflicts is crucial for the choice of the Lape people. This research is expected to provide theoretical implications on the development of political science, especially in rational choice studies and to be an input for policy makers in the prevention and management of land conflicts that occur in indigenous communities, especially in the Province of East Nusa Tenggara.